Strategi Pengembangan Usaha Kecil dan Menengah Kerupuk Kulit Desa Banjarwaru - Ujang Abdullah (Neolectura, 2022)
Skin crackers are one of the UMKM in Indonesia which are engaged in the food sector. The number of UMKM in Indonesia is very large, even UMKM are the main drivers of the community's economy in meeting their daily needs. With the existence of UMKM, an independent economy is increasingly created by developing. Skin crackers are one of the UMKM in Indonesia which are engaged in the food sector. The number of UMKM in Indonesia is very large, even UMKM are the main drivers of the community's economy in meeting their daily needs. One of the existing UMKM is skin crackers in the Bogor Regency area. The business has been around for a long time and this paper prepares a strategic analysis related to how to develop a business run by a leather cracker business owner at one point, which is in the Bogor Regency area, West Java Province. The method used in designing this scientific paper is to conduct interviews, surveys, observations and identification of the UMKM in question, as well as various information related to the business development strategy of leather cracker UMKM in Bogor Regency. The results of writing this scientific paper conclude that the strategy that needs to be improved from these SMEs is to improve the quality of human resources both knowledge and capability in advancing the business according to the times. Conduct product innovation and product differentiation.